ANALISIS WACANA KRITIS DALAM RUBRIK”PANDANGAN KAMI” SURAT KABAR “SUMATERA EKSPRES” EDISI AGUSTUS 2016 - asmah asmah (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2017)
Abstract: Studies on the critical discourse was mostly done by the researchers, evidenced by the many theses and thesis using discourse analysis as "tools / scalpel" in his studies. This study aims to describe and understand how critical discourse analysis to reveal the ideology of newspaper editors "Sumatra Ekspres" in the rubric "Our view" through the elements on the macro structure, superstructure, and microstructure. This research is descriptive-qualitative method of critical discourse analysis of Teun A. Van Dijk models. Data were collected by means of documentation (clipping) then recorded in a working paper based on the macro structure, superstructure, and microstructure.